Pakistani Government–News Media Relationships: How relevant are Western journalistic values?. (2nd January 2017) - Akhtar, Nadeem; Pratt, Cornelius B.
Abstract : This study investigates factors that contribute to the fraught relationships between the government and the news media in Pakistan. Responses from an online survey of 357 Pakistani journalists and educators indicate that (1) economic concerns are the focal point of government–news media relationships; (2) stiff competition among news organizations to provide platforms for government advertisements have affected journalistic standards; (3) higher government investment in advertisements resulted in governments receiving pro-government coverage; (4) private news media are coerced by the state through laws, regulations, licenses and taxes, leading to adversarial relationships between the news media and the government; (5) political affiliation, religion and national identity are the major influences on the journalists' worldviews; and (6) Western journalistic values do not seem to contribute significantly to developing universal journalistic values among Pakistani journalists in part because of cultural differences. The implications of these findings for journalism in Pakistan include having a better understanding of the plight of journalists and the media in that country and of the factors than can be considered to better improve government–media relationships.